Technical auditing of water supply systems – part 1: the complex methodology - Tuhovčák, Ladislav; Kučera, Tomáš; Sucháček, Tomáš (Water science & technology. Water supply, 2018)
To ensure the sustainability and reliability of water supply infrastructure, a basic pre-condition must be applied related to its continual renewal. For renewal planning, there are a number of methods, techniques and software tools for decision-support, but in many cases most of them focus only on water mains. However, water supply systems consist of more various parts and structures than simply water pipes. Therefore, it is not appropriate to invest in renewal planning for a single part of the water supply infrastructure only. An effective and detailed evaluation of the technical condition requires the deployment of specialists and a reliable database, as well as considerable amounts of time, instrumentation and software. Therefore, it is preferable to first perform a rapid and efficient preliminary identification of problematic areas and elements of the entire water supply system. This paper presents the methodology and Technical and Energy Audit (TEA Water), as well as an effective preliminary assessment of the technical condition of water supply systems (WSSs). The paper presents the structure of proposed technical indicators, the method of their determination and evaluation, as well as including a presentation of case studies.